Spectacle lens
By adopting a multi-layer composition coating structure in the glasses lens, using the combination of organic compounds, inorganic oxide particles and polymerization initiator, the problem of insufficient crack resistance and damage resistance in the prior art is solved, and a higher degree of Lens hardness and crack resistance.
Patent Information
- Application Number
- CN202380046617.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-10
AI Technical Summary
Existing glasses lenses have shortcomings in their crack resistance and damage resistance, making it difficult to effectively suppress crack generation and maintain hardness when damaged.
Using a multi-layer composition coating structure, including organic compound X, inorganic oxide particles Y, and a polymerization initiator, multiple resin layers are formed by layer-by-layer coating, and the mass ratio of the composition and the molar absorbance coefficient of the polymerization initiator are controlled. To enhance the crack and damage resistance of the lens.
It significantly improves the crack resistance and damage resistance of glasses lenses, ensuring that the lenses are not prone to cracks during use, and maintains high hardness and adhesion when damaged.
Smart Images

Figure CN119301485A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to eyeglass lenses. Background Art
[0002] Patent Document 1 discloses a hard coat layer formed by curing a composition containing inorganic oxide particles, an organic silicon compound, and the like.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2015 / 163465 Summary of the invention
[0006] The present disclosure relates to an eyeglass lens, which has an eyeglass lens substrate, a primer layer and a hard coating layer in sequence, wherein the hard coating layer comprises a plurality of resin layers formed by applying a multilayer composition, the composition comprising an organic compound X selected from the group consisting of polymerizable compounds and polymers thereof, an inorganic compound Y selected from the group consisting of inorganic oxide particles and silsesquioxanes, and a polymerization initiator, and when the composition comprises a polymer, at least a portion of the polymer can be combined with at least a portion of the inorganic compound Y, and the eyeglass lens satisfies conditions 1 and 2. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 An example of a cross section of a spectacle lens is shown. DETAILED DESCRIPTION
[0008] Hereinafter, the spectacle lenses of the present disclosure will be described in detail.
[0009] The eyeglass lens of the present disclosure is excellent in the suppression of crack generation and scratch resistance.
[0010] In the present specification, "to" means that the numerical values described before and after it are included as the lower limit and the upper limit.
[0011] In the present specification, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0012] In the present specification, examples of halogenation include fluorination, chlorination, bromination and iodination.
[0013] In the present specification, “(meth)acrylic” is a concept including both acrylic and methacrylic groups, and “(meth)acryloyl” is a concept including both acryloyl and methacryloyl groups.
[0014] In this specification, solid content refers to components other than solvents, and even if the properties of the components are liquid at normal temperature and pressure (25°C, 101.3 kPa), they are calculated as solid content. In addition, the solid content may also be a component that undergoes chemical changes during the curing process.
[0015] However, in the case where the composition and the mixture for active polymerization described later contain a specific compound selected from the group consisting of a surfactant that is liquid at room temperature and pressure, an active polymerization catalyst that is liquid at room temperature and pressure, and a co-catalyst that is liquid at room temperature and pressure, the above-mentioned specific compound is not included in the solid content of the composition and the mixture for active polymerization described later. For example, in a composition composed of an organic compound X, an inorganic compound Y, a polymerization initiator, and a surfactant that is liquid at room temperature and pressure, the total amount of the organic compound X, the inorganic compound Y, and the polymerization initiator corresponds to the solid content of the composition, and the amount of the surfactant that is liquid at room temperature and pressure does not correspond to the solid content of the composition.
[0016] [Spectacle lenses]
[0017] The spectacle lens has a spectacle lens substrate, a primer layer and a hard coating layer in this order.
[0018] Figure 1 is a cross-sectional view of one embodiment of a spectacle lens. Figure 1 The spectacle lens 10 shown includes, on both sides of the spectacle lens substrate 12 , a primer layer 14 disposed on the spectacle lens substrate 12 and a hard coating layer 16 disposed on the primer layer 14 .
[0019] Figure 1 The spectacle lens 10 shown has the primer layer 14 and the hard coating layer 16 disposed on both surfaces of the spectacle lens substrate 12 , but the above-mentioned layers may be disposed on only one surface of the spectacle lens substrate 12 .
[0020] Hereinafter, various components that can be included in eyeglass lenses will be described in detail.
[0021] <Condition 1>
[0022] The eyeglass lenses satisfy condition 1.
[0023] Condition 1: The mass ratio A (content of inorganic compound Y / content of organic compound X) of the content of inorganic compound Y to the content of organic compound X in the compositions used for forming the plurality of resin layers is different and is 0.7 to 5.3,
[0024] The mass ratio A of the composition used in forming the composition constituting each of the plurality of resin layers gradually increases from the primer layer side toward the side opposite to the primer layer side.
[0025] Preferred embodiments of the contents of the various components will be described later.
[0026] The mass ratio A varies among the compositions used for forming the plurality of resin layers, and is 0.7 to 5.3.
[0027] The different mass ratios A refer to different mass ratios A of the compositions used in the respective resin layers. That is, the respective resin layers constituting the plurality of resin layers are formed using compositions having different mass ratios A.
[0028] When the resin layer is formed using the composition from the primer layer side toward the side opposite to the primer layer side, the mass ratio A of the composition used in forming the resin layer closest to the primer layer side (resin layer adjacent to the primer layer) is preferably 0.7 to 2.0, more preferably 0.7 to 1.0.
[0029] The mass ratio A of the composition used to form the resin layer on the side opposite to the primer layer (when the eyeglass lens has an antireflection layer, the resin layer adjacent to the antireflection layer) is preferably 4.0 to 10.0, more preferably 4.0 to 5.3.
[0030] For example, when an eyeglass lens includes, in this order, an eyeglass lens substrate, a primer layer, a resin layer 1 formed using composition 1, a resin layer 2 formed using composition 2, and a resin layer 3 formed using composition 3, the composition used in forming the resin layer closest to the primer layer side refers to composition 1, and the composition used in forming the resin layer closest to the primer layer side refers to composition 3.
[0031] The mass ratio A of the composition used in forming each of the resin layers constituting the plurality of resin layers gradually increases from the primer layer side toward the side opposite to the primer layer side.
[0032] For example, in a case where a spectacle lens sequentially comprises a spectacle lens substrate, a primer layer, a resin layer 1 formed using a composition 1, a resin layer 2 formed using a composition 2, and a resin layer 3 formed using a composition 3, it means that the resin layer 1, the resin layer 2, and the resin layer 3 are formed from the primer layer side toward the side opposite to the primer layer side, and the mass ratio A of the composition 1, the mass ratio A of the composition 2, and the mass ratio A of the composition 3 gradually increase in that order.
[0033] It should be noted that, when calculating the mass ratio A, if the amounts of the organic compound X and the inorganic compound Y used in preparing the composition are known, the mass ratio A can be calculated from the amounts used.
[0034] <Condition 2>
[0035] The eyeglass lenses satisfy condition 2.
[0036] Condition 2: The polymerization initiator comprises a polymerization initiator V having a ratio of a molar absorption coefficient at a wavelength of 254 nm to a molar absorption coefficient at a wavelength of 365 nm (molar absorption coefficient at a wavelength of 254 nm / molar absorption coefficient at a wavelength of 365 nm) of 50 or more, and a polymerization initiator W having the above molar absorption coefficient ratio of less than 30,
[0037] The mass ratio B of the content of the polymerization initiator V to the content of the polymerization initiator W (the content of the polymerization initiator V / the content of the polymerization initiator W) is 0.2 to 0.8.
[0038] The polymerization initiator V is the molar absorption coefficient at a wavelength of 254 nm (unit: (mol / L) -1 cm -1 ) relative to the molar absorption coefficient at a wavelength of 365nm (unit: (mol / L) -1 cm -1 ) ratio is 50 or more.
[0039] The ratio of the molar absorption coefficients is 50 or more, preferably 100-500, and more preferably 120-300.
[0040] Examples of the polymerization initiator V include Ominirad 127 (manufactured by IGM Resins Co., Ltd.) and Ominirad 1173 (manufactured by IGM Resins Co., Ltd.).
[0041] The polymerization initiator W is a polymerization initiator having a ratio of a molar absorption coefficient at a wavelength of 254 nm to a molar absorption coefficient at a wavelength of 365 nm of less than 30.
[0042] The ratio of the molar absorption coefficients is less than 30, preferably 1.0-25, and more preferably 1.0-20.
[0043] Examples of the polymerization initiator W include Ominirad 819 (manufactured by IGM Resins Co., Ltd.) and Ominirad 369 (manufactured by IGM Resins Co., Ltd.).
[0044] The ratio of the molar absorption coefficients can be calculated, for example, by preparing a solution in which each polymerization initiator is dissolved in a solvent (such as acetonitrile), analyzing the solution using a spectrophotometer (U-4100, manufactured by Hitachi, Ltd.), measuring the molar absorption coefficients, and calculating from these values.
[0045] The mass ratio B is 0.2 to 0.8.
[0046] The mass ratio B of the composition used for forming the resin layer closest to the primer layer (resin layer adjacent to the primer layer) is preferably 0.2 to 0.6, and more preferably 0.2 to 0.4.
[0047] The mass ratio B of the composition used to form the resin layer on the side opposite to the primer layer (when the eyeglass lens has an antireflection layer, the resin layer adjacent to the antireflection layer) is preferably 0.3 to 0.8, more preferably 0.7 to 0.8.
[0048] The mass ratio B of the composition used to form each of the plurality of resin layers preferably increases gradually from the primer layer side toward the side opposite to the primer layer side. The description of the mass ratio A mentioned above can be referred to for the description of the gradual increase.
[0049] <Spectacle lens substrate>
[0050] The spectacle lens has a spectacle lens substrate.
[0051] The eyeglass lens substrate is a member that supports the primer layer, hard coat layer, etc.
[0052] Examples of the types of spectacle lens substrates include those made of organic materials or inorganic materials, and those made of inorganic materials (eg, glass substrates) are preferred.
[0053] As eyeglass lens substrates, for example, there can be mentioned finished lenses whose convex and concave surfaces are both optically finished and formed according to the desired diopter, semi-finished lenses whose convex surface only is finished as an optical surface (such as a spherical surface, a rotational aspherical surface, and a progressive surface, etc.), and semi-finished lenses whose concave surfaces are processed and ground according to the wearer's prescription.
[0054] Examples of organic materials (so-called resins) include (meth)acrylic resins, thiourethane resins, allyl resins, episulfide resins, polycarbonate resins, polyurethane resins, polyester resins, polystyrene resins, polyethersulfone resins, poly-4-methylpentene-1 resins, and diethylene glycol bisallyl carbonate resins (CR-39).
[0055] Examples of the inorganic material include silicon, ceramics, and glass, and glass is preferred.
[0056] The thickness of the spectacle lens substrate may be 1 to 30 mm in terms of workability.
[0057] The thickness (average thickness) can be determined, for example, by measuring thicknesses at five arbitrary points and taking the arithmetic average of the thicknesses.
[0058] The spectacle lens substrate preferably has light transmittance, and may be transparent or opaque. In addition, it may be colored.
[0059] <Primer layer>
[0060] The eyeglass lenses have a primer layer.
[0061] The primer layer is a layer that improves the adhesion of the hard coat layer to the spectacle lens substrate.
[0062] Examples of the material constituting the primer layer include resins, and specific examples thereof include urethane resins, epoxy resins, phenol resins, polyimide resins, polyester resins, bismaleimide resins, and polyolefin resins.
[0063] The thickness of the primer layer may be 0.3 to 2 μm.
[0064] The thickness (average thickness) can be measured by the same method as the thickness of the spectacle lens substrate.
[0065] <Hard Coating>
[0066] Eyeglass lenses have a hard coating.
[0067] The hard coat layer is a layer disposed on the primer layer, and is a layer that imparts scratch resistance to the eyeglass lens substrate.
[0068] The hard coat layer includes a plurality of resin layers formed by applying a plurality of layers of a composition described later.
[0069] The number of resin layers constituting the hard coat layer is preferably 2 or more, more preferably 3 to 5.
[0070] The thickness of the hard coat layer is preferably 1 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. The upper limit is preferably 30 μm or less. It should be noted that the thickness of the hard coat layer corresponds to the total thickness of the multiple resin layers of the hard coat layer.
[0071] The thickness (average thickness) can be measured by the same method as the thickness of the spectacle lens substrate.
[0072] The thickness of each of the plurality of resin layers constituting the hard coat layer may be the same or different.
[0073] The hard coat layer preferably contains various components that may be contained in the composition described later, and cured products thereof and decomposed products thereof.
[0074] (Composition)
[0075] The composition comprises an organic compound X, an inorganic compound Y and a polymerization initiator.
[0076] By applying the composition in multiple layers, a plurality of resin layers (hard coat layers) can be formed.
[0077] When the mixture after reacting the living polymerization mixture described later is used to prepare the composition, part or all of the organic compound X, inorganic compound Y and polymerization initiator contained in the composition may be the unreacted components of the organic compound X, inorganic compound Y and polymerization initiator contained in the mixture after the above reaction.
[0078] -Organic Compound X-
[0079] The composition comprises an organic compound X.
[0080] The organic compound X is an organic compound selected from the group consisting of polymerizable compounds and polymers thereof. That is, the organic compound X may be a polymerizable compound or a polymer obtained by polymerizing a polymerizable compound.
[0081] The polymerizable compound is preferably a monomer or oligomer having a polymerizable group.
[0082] The polymerizable group may be any of a radical polymerizable group and a cation polymerizable group.
[0083] Examples of the radical polymerizable group include ethylenically unsaturated groups such as a (meth)acryloyl group, a vinyl group, and a styryl group, and a (meth)acryloyl group is preferred.
[0084] Examples of the cationically polymerizable group include alicyclic ether groups such as an epoxy group and an oxetanyl group, a cyclic acetal group, a cyclic lactone group, a cyclic thioether group, a spiroorthoester group, and a vinyloxy group. An epoxy group or an oxetanyl group is preferred.
[0085] The polymerizable compound may be any of a monofunctional polymerizable compound and a polyfunctional polymerizable compound, but a polyfunctional polymerizable compound is preferred.
[0086] When a polyfunctional polymerizable compound is used, a branched structure and / or a network structure (crosslinked structure) can be introduced into the obtained polymer, and excellent scratch resistance can be obtained.
[0087] The number of ethylenically unsaturated groups contained in the polymerizable compound is preferably 1 or 2 or more, more preferably 2 to 5.
[0088] The polymerizable compound may have other functional groups in addition to the polymerizable group. Examples of the other functional groups include a urethane bond, a hydroxyl group, and ethylenically unsaturated groups such as a vinyl group and a styryl group, and a urethane bond is preferred.
[0089] The polymerizable compound is preferably one or more selected from the group consisting of compounds represented by formula (1) and compounds represented by formula (2).
[0090]
[0091] In formula (1), X and Y each independently represent a hydrogen atom or a substituent.
[0092] The substituent represented by X is preferably an organic group, and more preferably a methyl group.
[0093] The substituent represented by Y is preferably an organic group, more preferably an alkyl group which may have a substituent or a cycloalkyl group which may have a substituent, and further preferably a cycloalkyl group which may have a substituent. In addition, the substituent represented by Y may be an organic group having a carbamate group.
[0094] The alkyl group may be linear or branched, and preferably has 1 to 10 carbon atoms.
[0095] The cycloalkyl group may be monocyclic or polycyclic. The cycloalkyl group preferably has 3 to 12 carbon atoms.
[0096] However, Y is not a group having an ethylenically unsaturated group.
[0097] In formula (2), k represents an integer greater than 2. Z represents a k-valent linking group. When k is 2, Z may be a single bond. X represents a hydrogen atom or a substituent.
[0098] k is preferably an integer of 2 to 10, more preferably 2 or 3, and even more preferably 2.
[0099] The substituent represented by X is preferably an organic group, more preferably a methyl group. In formula (2), a plurality of Xs may be the same or different.
[0100] Z may be a k-valent organic group. The number of atoms other than hydrogen atoms possessed by the k-valent linking group is preferably 1 to 500.
[0101] Examples of k-valent linking groups include ether groups (-O-), carbonyl groups (-CO-), ester groups (-COO-), sulfide groups (-S-), carbamate groups (-NHCOO-), -SO2-, -NR N -(R N represents a hydrogen atom or a substituent), a divalent linking group such as an alkylene group (preferably having 1 to 10 carbon atoms), an alkenylene group (preferably having 2 to 10 carbon atoms) and an alkynylene group (preferably having 2 to 10 carbon atoms); a trivalent linking group having a group represented by "-N<" and a trivalent linking group having a group represented by "-CR<" (R represents a hydrogen atom or a substituent); a quadrivalent linking group having a group represented by ">C<"; a k-valent linking group having a cyclic group such as an aromatic ring group and an alicyclic group; and a group formed by combining them.
[0102] The ring constituting the above-mentioned k-valent linking group having a ring group may have a heteroatom.
[0103] Examples of the aromatic ring group include a benzene ring, a naphthalene ring, and a bisphenol ring group such as a ring group formed by removing an arbitrary hydrogen atom from a bisphenol compound such as bisphenol A.
[0104] Examples of the alicyclic group include cycloalkane ring groups such as a cyclohexane ring group, a cyclopentane ring group, and a tricyclodecane ring group, a dioxane ring group, and an isocyanurate ring group.
[0105] The above-mentioned alkylene group, the above-mentioned alkenylene group, the above-mentioned alkynylene group and the above-mentioned cyclic group may further have a substituent.
[0106] The k-valent linking group may have one or more groups selected from the group consisting of an alkylene group, a (poly)oxyalkylene group, and a urethane bond.
[0107] The k atoms in Z that are directly bonded to the group represented by "CH2=CX-CO-" may be oxygen atoms.
[0108] The polyfunctional polymerizable compound is preferably one or more selected from the group consisting of compounds represented by formula (I) and compounds represented by formula (II), and is more preferably a compound represented by formula (I).
[0109]
[0110] In formula (I), m represents an integer of 0 to 9. R represents a bifunctional polyester polyol residue or a bifunctional polyether polyol residue. 1 represents a hydrogen atom or a methyl group. 2 represents an alkylene group having 2 to 4 carbon atoms. L represents a group represented by any one of formulae (I-1) to (I-3).
[0111] In the formula (I), R represents a bifunctional polyester polyol residue or a bifunctional polyether polyol residue.
[0112] The bifunctional polyester polyol residue is a group obtained by removing two hydroxyl groups (OH) from a polyester polyol having two hydroxyl groups. Examples of the polyester polyol include polyester polyols obtained by dehydration condensation of adipic acid or phthalic acid with a diol having 2 to 6 carbon atoms.
[0113] The bifunctional polyether polyol residue is a group obtained by removing two hydroxyl groups (OH) from a polyether polyol having two hydroxyl groups. Examples of the polyether polyol include polyethylene glycol and polypropylene glycol.
[0114] In formula (I), R 2 It represents an alkylene group having 2 to 4 carbon atoms.
[0115] The alkylene group may be either linear or branched.
[0116] L represents a group represented by any one of formula (I-1) to formula (I-3).
[0117] In formula (I-1) to formula (I-3), * represents a binding position.
[0118] When there are a plurality of groups represented by the same symbol in formula (I), the plurality of groups represented by the same symbol may be the same as or different from each other.
[0119]
[0120] In formula (II), n represents an integer of 0 to 9. 3 and R 4 Each independently represents a hydrogen atom or a methyl group.
[0121] When a plurality of groups represented by the same symbol exist in formula (II), the plurality of groups represented by the same symbol may be the same as or different from each other.
[0122] The polymer is not particularly limited as long as it is a polymer obtained by polymerizing the polymerizable compound by a known method. As the polymer, a polymer obtained by living radical polymerization is preferred.
[0123] The organic compound X may be used alone or in combination of two or more.
[0124] The content of the organic compound X is preferably 20% by mass to 90% by mass, more preferably 30% by mass to 80% by mass, based on the total solid content of the composition.
[0125] -Inorganic compound Y-
[0126] The composition comprises an inorganic compound Y.
[0127] The inorganic compound Y is an inorganic compound selected from the group consisting of inorganic oxide particles and silsesquioxane.
[0128] It should be noted that silsesquioxane is not included in the inorganic oxide particles.
[0129] The inorganic oxide particles may be metal oxide particles.
[0130] Examples of inorganic oxide particles include oxide particles of one or more metals selected from the group consisting of Ti, Zr, Si, Al, Sn, Sb, Ta, Ce, La, Fe, Zn, W and In, and composite metal oxide particles thereof. Composite metal oxide particles refer to oxide particles containing two or more metals (metal atoms).
[0131] The inorganic oxide particles may contain one or more selected from the group consisting of SiO2 (silicon oxide), Al2O3 (aluminum oxide), SnO2 (tin oxide), ZrO2 (zirconium oxide) and TiO2 (titanium oxide), more preferably contain one or more selected from the group consisting of SiO2 and ZrO2, and further preferably contain SiO2.
[0132] Commercially available inorganic oxide particles may be used. Examples of commercially available inorganic oxide particles include sols in which one or more inorganic oxide particles selected from the group consisting of SiO2, Al2O3, SnO2, ZrO2, TiO2, and composite oxide particles thereof are dispersed in water or an organic solvent.
[0133] Silsesquioxane refers to a silane compound having a basic skeleton represented by formula (Q) obtained by hydrolyzing a trifunctional silane compound such as alkoxysilane, chlorosilane and silanol.
[0134] Examples of the structure of silsesquioxane include irregular forms such as a random structure, a ladder structure, a cage-type (completely condensed cage-type) structure, and an incomplete cage-type structure (a partially cleaved structure of a cage-type structure, i.e., a structure in which a part of silicon atoms in the cage-type structure is missing and a structure in which a part of silicon-oxygen bonds in the cage-type structure are cut).
[0135] R Q -SiO 3 / 2 (Q)
[0136] In formula (Q), R Q It represents a monovalent organic group.
[0137] As silsesquioxane, for example, SQ series (for example, AC-SQ series and MAC-SQ series, etc., manufactured by Toagosei Co., Ltd.) can be mentioned.
[0138] The inorganic compound Y may also be surface-treated.
[0139] The surface treatment is not included in the mode in which at least a part of the polymer of the organic compound X is bonded to at least a part of the inorganic compound Y described later.
[0140] Examples of the surface treatment include introduction of various functional groups and treatment using a known surface modifying agent.
[0141] Examples of the surface-treated inorganic compound Y include inorganic compounds Y having an initiation site on the surface as described later.
[0142] At least a part of the inorganic compound Y and at least a part of the polymer as the organic compound X may be bonded to each other.
[0143] Examples of the bonding method include covalent bonding, coordination bonding, ionic bonding, hydrogen bonding, van der Waals bonding, and metallic bonding, and a covalent bond is preferred.
[0144] When the polymer as the organic compound X is bonded to the inorganic oxide particles, it is preferred that the polymer as the organic compound X is bonded to the surface of the inorganic oxide particles. In other words, in the composition, the polymer as the organic compound X is bonded to the inorganic oxide particles, and modified inorganic oxide particles including the inorganic oxide particles and the polymer as the organic compound X bonded to the surface of the inorganic oxide particles can be constituted.
[0145] In addition, when the polymer as the organic compound X is bonded to the silsesquioxane, it is preferred that the polymer as the organic compound X is bonded to the surface of the silsesquioxane. In other words, in the composition, the polymer as the organic compound X is bonded to the silsesquioxane, and a modified silsesquioxane including the silsesquioxane and the polymer as the organic compound X bonded to the surface of the silsesquioxane can be constituted.
[0146] As described above, when the polymer is bonded to the inorganic compound Y, the two may be bonded via other organic compounds. For example, when the inorganic compound Y having a starting site on the surface is bonded to the polymer as the organic compound X, the inorganic compound Y may be bonded to the polymer as the organic compound X via the starting site.
[0147] Hereinafter, the modified inorganic oxide particles and the modified silsesquioxane are also collectively referred to as “modified inorganic compound Y”.
[0148] As the modified inorganic compound Y, a separately prepared modified inorganic compound Y may be used, or a modified inorganic compound Y obtained by reacting the polymerizable compound in the composition with the inorganic compound Y may be used.
[0149] The modified inorganic compound Y is preferably obtained by living radical polymerization. If the polymerization is carried out by living radical polymerization, the molecular weight distribution of the obtained polymer can be narrowed, the modified inorganic compound Y can be uniformly dispersed in the composition and the resin layer, and the hardness of the hard coat layer can be easily improved.
[0150] The average particle size of the inorganic compound Y is preferably 0.5 to 200 nm, more preferably 1 to 50 nm.
[0151] Examples of a method for measuring the average particle size include a method of measuring the particle sizes of arbitrary 100 inorganic compounds Y using a scanning electron microscope and calculating the arithmetic average thereof and a method of measuring under the following conditions using a dynamic light scattering method.
[0152] Measuring device: Zeta potential / particle size measuring system ELS-Z2 (manufactured by Otsuka Electronics Co., Ltd.)
[0153] Measurement cell: Particle size cell unit (scattering angle 165°)
[0154] Measurement temperature: 25℃
[0155] Particle size analysis method: Contin method
[0156] During the measurement, the inorganic compound Y to be measured or the dispersion containing the inorganic compound Y to be measured is diluted with a dilution solvent as needed. As the dilution solvent, for example, MEK (methyl ethyl ketone) is used. In the case where the use of MEK causes problems such as aggregation of the inorganic compound Y, other appropriate dilution solvents are used.
[0157] In addition, in the present disclosure, unless otherwise specified, the average particle size means an average particle size based on volume distribution.
[0158] The inorganic compound Y may be used alone or in combination of two or more.
[0159] The content of the inorganic compound Y is preferably 10% by mass to 60% by mass, more preferably 10% by mass to 50% by mass, based on the total solid content of the composition.
[0160] -Polymerization initiator-
[0161] The composition includes a polymerization initiator.
[0162] Examples of the polymerization initiator include the above-mentioned polymerization initiator V and the above-mentioned polymerization initiator W.
[0163] Furthermore, the polymerization initiator may contain other polymerization initiators other than the polymerization initiator V and the polymerization initiator W as long as the condition 2 is satisfied.
[0164] The polymerization initiator W and the polymerization initiator V may be used alone or in combination of two or more.
[0165] The content of the polymerization initiator W is preferably 0.1 to 3.0% by mass, more preferably 0.1 to 1.0% by mass, based on the total solid content of the composition.
[0166] The content of the polymerization initiator V is preferably 0.1 to 3.0% by mass, more preferably 0.1 to 1.0% by mass, based on the total solid content of the composition.
[0167] -Sensitizer-
[0168] The composition may comprise a sensitizer.
[0169] As a sensitizer, Anthracure series (made by Kawasaki Chemical Industries, Ltd.) is mentioned, for example.
[0170] The sensitizer may be used alone or in combination of two or more.
[0171] When the composition contains a sensitizer, the content of the sensitizer is preferably 0.001 to 5% by mass, more preferably 0.05 to 2% by mass, based on the total solid content of the composition.
[0172] -Surfactant-
[0173] The composition may comprise a surfactant.
[0174] Examples of the surfactant include organic silicon compounds such as silicone oil, and specific examples include DOWSIL series (manufactured by Dow Chemical).
[0175] The surfactant may be used alone or in combination of two or more.
[0176] When the composition contains a surfactant, the content of the surfactant is preferably 0.001 to 5% by mass, more preferably 0.01 to 0.5% by mass, based on the total solid content of the composition.
[0177] -UV absorber-
[0178] The composition may contain a UV absorber.
[0179] Examples of the ultraviolet absorber include triazine compounds and benzotriazole compounds.
[0180] Examples of the triazine compound and the benzotriazole compound include the triazine compound that may be contained in the mixture for living polymerization described below and the benzotriazole compound described below.
[0181] When a mixture for living polymerization is used in the preparation of the composition, the triazine compound and the benzotriazole compound contained in the mixture for living polymerization can be used as the ultraviolet absorber in the composition.
[0182] The ultraviolet absorber may be used alone or in combination of two or more.
[0183] When the composition contains a UV absorber, the content of the UV absorber is preferably 0.01 to 5% by mass, more preferably 0.1 to 3% by mass, based on the total solid content of the composition.
[0184] -Solvents-
[0185] The composition may comprise a solvent.
[0186] Examples of the solvent include water and organic solvents.
[0187] Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, hydrocarbon solvents, halogenated hydrocarbon solvents, amide solvents, sulfone solvents, and sulfoxide solvents.
[0188] The solvent may be used alone or in combination of two or more.
[0189] When the composition contains a solvent, the content of the solvent is preferably 10% by mass to 90% by mass, and more preferably 20% by mass to 60% by mass, based on the total mass of the composition.
[0190] -Other ingredients-
[0191] The composition may contain various components that may be contained in the mixture for living polymerization described later, and their reactants and their decomposition products.
[0192] The composition may contain additives such as an anti-aging agent, a coating film adjusting agent, a light stabilizer, an antioxidant, an anti-coloring agent, a dye, a filler, and an internal mold release agent in addition to the various components described above, as necessary.
[0193] <Anti-reflection layer>
[0194] Spectacle lenses may have an anti-reflective layer.
[0195] The spectacle lens may have an antireflection layer on the hard coating layer, that is, may have a spectacle lens substrate, a primer layer, a hard coating layer, and an antireflection layer in this order.
[0196] The structure of the antireflection layer may be either a single-layer structure or a multi-layer structure.
[0197] As the antireflection layer, an inorganic antireflection layer is preferred. The inorganic antireflection layer refers to an antireflection layer composed of an inorganic compound.
[0198] The multi-layer antireflection layer may be a structure in which low-refractive index layers and high-refractive index layers are alternately stacked.
[0199] Examples of the material constituting the high refractive index layer include titanium, zircon, aluminum, niobium, tantalum, and lanthanum oxides, and examples of the material constituting the low refractive index layer include silicon dioxide oxides.
[0200] Examples of a method for forming the antireflection layer include dry methods such as vacuum deposition, sputtering, ion plating, ion beam assist, and CVD.
[0201] [Method for manufacturing eyeglass lenses]
[0202] The method for producing the spectacle lenses is not particularly limited, and a known production method may be used.
[0203] The method for producing the eyeglass lens may be a method of forming each layer by applying the primer layer-forming composition or the compositions in sequence.
[0204] For example, there can be mentioned a method for producing an eyeglass lens comprising the steps of applying a primer layer-forming composition on an eyeglass lens substrate to form a primer layer and applying a multilayer composition on the primer layer to form a hard coat layer.
[0205] After the coating film is formed, a drying treatment such as a heating treatment or a curing treatment such as curing the coating film may be performed as necessary in order to remove the solvent from the coating film.
[0206] The primer layer-forming composition preferably contains the above-mentioned components that the primer layer may have and a solvent. The composition is as described above.
[0207] Examples of a method for applying the primer layer-forming composition or the composition include a dip coating method, a spin coating method, a spray coating method, an inkjet coating method, and a flow coating method.
[0208] For example, when the dip coating method is used, the spectacle lens substrate is immersed in the primer layer forming composition or the composition, and then the spectacle lens substrate is lifted up and dried, thereby forming a coating film of a predetermined thickness on the spectacle lens substrate.
[0209] The thickness of the coating film formed on the spectacle lens substrate can be adjusted appropriately.
[0210] The multilayer coating in the step of forming the hard coat layer may be either simultaneous multilayer coating or sequential multilayer coating.
[0211] When the multilayer coating is a sequential multilayer coating, it is preferred to perform the curing treatment described below after coating all the compositions. For example, when each resin layer is formed using each composition, it is preferred to perform the curing treatment after coating each composition to form each coating film.
[0212] The curing treatment may be a light irradiation treatment.
[0213] The conditions for the light irradiation treatment can be selected according to the type of the polymerization initiator.
[0214] Examples of the type of light used for light irradiation include ultraviolet rays and visible rays.
[0215] As a light source for light irradiation, a high-pressure mercury lamp is mentioned, for example.
[0216] From the perspective of productivity and curability of the coating film, the cumulative amount of light irradiation may be 100 to 3000 mJ / cm 2 , more preferably 100 to 1500 mJ / cm 2 .
[0217] The method for manufacturing the spectacle lens may be as follows.
[0218] A method for manufacturing a spectacle lens, wherein the spectacle lens sequentially comprises a spectacle lens substrate, a primer layer, and a hard coating layer composed of a plurality of resin layers, the manufacturing method comprising:
[0219] A step of forming the primer layer on the spectacle lens substrate; and
[0220] a step of applying a multilayer composition on the primer layer to form a plurality of resin layers,
[0221] The composition comprises an organic compound X selected from the group consisting of polymerizable compounds and polymers thereof, an inorganic compound Y selected from the group consisting of inorganic oxide particles and silsesquioxane, and a polymerization initiator.
[0222] In the case where the composition includes a polymer, at least a portion of the polymer and at least a portion of the inorganic compound Y may be combined,
[0223] The spectacle lens satisfies conditions 1 and 2.
[0224] Condition 1: The mass ratio A of the content of the inorganic compound Y to the content of the organic compound X in the composition used for forming the plurality of resin layers is different from each other and is 0.7 to 5.3,
[0225] The mass ratio A of the composition used in forming each of the resin layers constituting the plurality of resin layers gradually increases from the primer layer side toward the side opposite to the primer layer side.
[0226] Condition 2: The polymerization initiator includes a polymerization initiator V having a ratio of a molar absorption coefficient at a wavelength of 254 nm to a molar absorption coefficient at a wavelength of 365 nm of 50 or more, and a polymerization initiator W having a ratio of a molar absorption coefficient of less than 30,
[0227] The mass ratio B of the content of the polymerization initiator V to the content of the polymerization initiator W is 0.2 to 0.8.
[0228] <Primer layer forming composition or method for producing the composition>
[0229] As a method for producing the primer layer-forming composition or the composition, for example, the above-mentioned primer layer-forming composition or various components that can be contained in the composition may be mixed at once, or the various components may be mixed separately and stepwise.
[0230] <Method for producing modified inorganic compound Y)>
[0231] The method for producing the modified inorganic compound Y may be a method of polymerizing a polymerizable compound on the surface of the inorganic compound Y by living radical polymerization to bond a polymer.
[0232] The living radical polymerization may be atom transfer radical polymerization.
[0233] Specifically, it can be produced by reacting a mixture for living polymerization containing an inorganic compound Y having an initiation site on the surface, a polymerizable compound, and an living polymerization catalyst.
[0234] Hereinafter, as one embodiment of the method for producing the modified inorganic compound Y, a method for producing the modified inorganic compound Y by reacting the above-mentioned mixture for living polymerization, polymerizing the polymerizable compound by living radical polymerization, and bonding the polymer will be described in detail.
[0235] (Mixture for living polymerization)
[0236] The mixture for living polymerization preferably contains an inorganic compound Y having an initiation site on the surface, a polymerizable compound, and a living polymerization catalyst.
[0237] -Inorganic compound Y having an initiation site on the surface-
[0238] The mixture for living polymerization may contain an inorganic compound Y having an initiation site on the surface.
[0239] The inorganic compound Y having an initiation site on the surface refers to an inorganic compound Y having a group that serves as a starting point for living radical polymerization on the surface.
[0240] The inorganic compound Y is as described above.
[0241] As the starting site, for example, a halogenated organic group can be mentioned.
[0242] The starting site is preferably a site having a group represented by formula (S1).
[0243]
[0244] In formula (S1), * represents a bonding position. X represents a halogen atom. R S1 and R S2 Each independently represents a hydrogen atom or a substituent. S1 It represents a divalent linking group.
[0245] The substituent is preferably an organic group, more preferably a hydrocarbon group. The substituent has preferably 1 to 20 carbon atoms.
[0246] As the divalent linking group, for example, a divalent linking group represented by Z can be mentioned.
[0247] As a method for producing an inorganic compound Y having an initial site on the surface, for example, a method in which an epihalohydrin (e.g., epichlorohydrin, etc.) is reacted with an inorganic compound Y having a group containing an ethylenically unsaturated group (e.g., a (meth)acryloyl group, etc.) on the surface of the inorganic compound Y in the presence of aluminum trichloride can be cited.
[0248] In this case, the content of the inorganic compound Y having an ethylenically unsaturated group fixed to the surface is preferably 70 to 99.9% by mass relative to the total content of the inorganic compound Y having an ethylenically unsaturated group fixed to the surface, aluminum chloride and epihalohydrin.
[0249] The content of aluminum trichloride is preferably 0.001 to 5% by mass relative to the above total content.
[0250] The content of the epihalohydrin is preferably 0.05 to 30% by mass relative to the above total content.
[0251] After a reaction for producing an inorganic compound Y having an initiation site on the surface is carried out using a composition comprising an inorganic compound Y having an ethylenically unsaturated group fixed on the surface, aluminum chloride and epihalohydrin, the composition subjected to the reaction can be directly used for preparing a mixture for living polymerization.
[0252] The inorganic compound Y having an ethylenically unsaturated group fixed to the surface can be prepared, for example, by reacting the inorganic compound Y with a silane coupling agent having an ethylenically unsaturated group (eg, (meth)acryloyl group), or a commercially available product can be used.
[0253] The inorganic compound Y having a starting site on the surface may be used alone or in combination of two or more.
[0254] When the living polymerization mixture contains the inorganic compound Y having an initiation site on the surface, the content of the inorganic compound Y having an initiation site on the surface is preferably 20 to 99.5% by mass, more preferably 30 to 96% by mass, based on the total solid content of the living polymerization mixture.
[0255] -Polymerizable compounds-
[0256] The mixture for living polymerization may contain a polymerizable compound.
[0257] Examples of the polymerizable compound include the above-mentioned polymerizable compounds, and preferred embodiments are also the same.
[0258] The polymerizable compound may be used alone or in combination of two or more.
[0259] When the mixture for living polymerization contains a polymerizable compound, the content of the polymerizable compound is preferably 0.1 to 60% by mass, more preferably 10 to 60% by mass, based on the total solid content of the mixture for living polymerization.
[0260] -Active polymerization catalyst-
[0261] The mixture for living polymerization may contain an active polymerization catalyst.
[0262] Examples of the active polymerization catalyst include transition metals and transition metal compounds.
[0263] Examples of the transition metal in the above transition metal and transition metal compound include copper, iron, cobalt, chromium, manganese, molybdenum, silver, zinc, palladium, rhodium, platinum, ruthenium, iridium, ytterbium, samarium, rhenium and nickel, and copper, iron or ruthenium is preferred.
[0264] The above transition metal compound may be a transition metal complex composed of the above transition metal and a ligand.
[0265] The active polymerization catalyst may be an iron compound (eg, ferrocenes, etc.).
[0266] The above-mentioned iron compound may be any one of the compound represented by the formula (F1) and the compound represented by the formula (F2).
[0267] CP 1 -Fe-CP 2 (F1)
[0268] CP 1 -Fe-(R)3 (F2)
[0269] In formula (F1), CP 1 and CP 2 Each independently represents a cyclopentadienyl ring which may have a substituent.
[0270] The number of substituents on the cyclopentadienyl ring is preferably 0 to 5, more preferably 1.
[0271] The cyclopentadienyl ring may have a substituent group of -P(R P )2.
[0272] The above-mentioned “-P(R P )2”, P is a phosphorus atom, and 2 R PEach independently represents a hydrogen atom or a substituent. The substituent is preferably an organic group, more preferably an alkyl group or a phenyl group. The alkyl group may be straight-chain or branched. The number of carbon atoms in the alkyl group is preferably 1 to 3.
[0273] In formula (F1), "Fe" is an iron atom.
[0274] In formula (F2), CP 1 represents a cyclopentadienyl ring which may have a substituent. Three Rs each independently represent -CO, a halogen atom or -PPh3.
[0275] In formula (F2), CP 1 With CP in formula (F1) 1 The preferred ranges are the same.
[0276] In the above-mentioned "-PPh3", P is a phosphorus atom, and Ph is a phenyl group which may have a substituent. The above-mentioned substituent is preferably an organic group, and more preferably an alkyl group. The above-mentioned alkyl group may be either linear or branched. The number of carbon atoms of the above-mentioned alkyl group is preferably 1 to 3. The number of substituents possessed by the above-mentioned phenyl group is preferably 0 to 5.
[0277] In formula (F2), "Fe" is an iron atom.
[0278] The active polymerization catalyst may be copper or a copper compound.
[0279] Examples of the copper compound include cuprous chloride, cuprous bromide, cuprous iodide, cuprous cyanide, cuprous oxide, and cuprous perchlorate.
[0280] The active polymerization catalysts may be used alone or in combination of two or more.
[0281] When the mixture for living polymerization contains an living polymerization catalyst, the content of the living polymerization catalyst is preferably 0.0001 to 1% by mass, more preferably 0.005 to 0.2% by mass, based on the total solid content of the mixture for living polymerization.
[0282] -Co-catalyst-
[0283] The mixture for living polymerization may contain a cocatalyst.
[0284] Examples of the co-catalyst include triazine compounds, benzotriazole compounds and imidazole compounds.
[0285] The triazine compound is a compound having at least one triazine ring.
[0286] The benzotriazole compound is a compound having at least one benzotriazole ring.
[0287] The imidazole compound is a compound having at least one imidazole ring.
[0288] As the co-catalyst, a commercially available product can be used.
[0289] Examples of the co-catalyst include Tinuvin 400, Tinuvin 384-2, and Tinuvin 477 (manufactured by BASF).
[0290] The co-catalyst may be used alone or in combination of two or more.
[0291] When the mixture for living polymerization contains a co-catalyst, the content of the co-catalyst is preferably 0.0001 to 10% by mass, more preferably 0.0001 to 5% by mass, based on the total solid content of the mixture for living polymerization.
[0292] When the mixture for living polymerization contains an active polymerization catalyst, the content of the active polymerization catalyst is preferably 50 to 99.99% by mass, more preferably 80 to 99.99% by mass, based on the total content of the co-catalyst and the active polymerization catalyst.
[0293] -Solvents-
[0294] The mixture for living polymerization may contain a solvent.
[0295] Examples of the solvent include ethyl acetate, toluene, acetone, dimethylformamide, ketones, alcohols and water.
[0296] The solvent may be used alone or in combination of two or more.
[0297] When the mixture for living polymerization contains a solvent, the content of the solvent is preferably 20% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, based on the total mass of the mixture for living polymerization.
[0298] The reaction time of the living polymerization may be 1 to 10 hours.
[0299] The reaction temperature of the living polymerization may be 25°C to 60°C.
[0300] [Example]
[0301] Hereinafter, the spectacle lenses of the present disclosure will be described in further detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples at all.
[0302] <Method of making eyeglass lenses 1>
[0303] The eyeglass lenses of Example 1 were manufactured according to the following manufacturing method 1.
[0304] (Formation of Primer Layer)
[0305] -Preparation of a primer layer-forming composition
[0306] Silwet L-77 (manufactured by Momentive) (0.2 parts by mass) and DOWSIL L-7604 (manufactured by Dow) (0.2 parts by mass) as surfactants, propylene glycol monomethyl ether (10.6 parts by mass) and an aqueous urethane dispersion (EVAFANOL HA170, manufactured by Nikka Chemical Co., Ltd., solid content 37% by mass) (200 parts by mass) were added to pure water (289 parts by mass) and stirred to prepare a primer layer-forming composition having a solid content concentration of 14.8% by mass.
[0307] -Formation of primer layer-
[0308] The eyeglass lens substrate shown below was immersed in the primer layer-forming composition at 90 mm / min and fired at 90° C. for 20 minutes to obtain an eyeglass lens substrate with a primer layer having primer layers on both surfaces of the eyeglass lens substrate.
[0309] When producing the eyeglass lens used for the evaluation of heat resistance described later, an eyeglass lens substrate having a refractive index of 1.60 (S0.00D, Nikon Lite 3AS blank, manufactured by Nikon Essilor Corporation) was used as the eyeglass lens substrate.
[0310] When producing eyeglass lenses used for evaluation of adhesion, cracking, and scratch resistance (pencil hardness) described later, an eyeglass lens substrate having a refractive index of 1.74 (S-7.00D, manufactured by Nikon Essilor Corporation) was used as the eyeglass lens substrate.
[0311] (Formation of hard coat layer)
[0312] - Preparation of Composition -
[0313] A composition 1 used for forming the resin layer 1A constituting the hard coat layer is prepared.
[0314] Chlorine addition of silsesquioxane and SiO2 particles
[0315] Acryloyl-coated SiO2 nanoparticle dispersion (MEK-AC-4130Y) (manufactured by Nissan Chemical Co., Ltd.) (212.7 parts by mass), ACSQ-TA100 (manufactured by Toagosei Co., Ltd.) (16.7 parts by mass), 1% AlCl3 solution (19.0 parts by mass) and epichlorohydrin (manufactured by Tokyo Chemical Industry Co., Ltd.) (2.73 parts by mass) were sequentially mixed and stirred at 40°C for 4 hours. The obtained solution was referred to as solution 1. Through the above reaction, SiO2 nanoparticles having a chlorine group (more specifically, SiO2 nanoparticles having a group represented by formula (S1) in which X is Cl) and / or silsesquioxanes having a chlorine group (more specifically, silsesquioxanes having a group represented by formula (S1) in which X is Cl) were obtained.
[0316] In addition, the solid content (nanoparticle content) of MEK-AC-4130Y was 30 mass %.
[0317] Living free radical polymerization
[0318] The obtained solution 1 (total parts by mass), NK oligomer UA-122P (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) (15.2 parts by mass), 1% Fe solution (3.00 parts by mass) and 0.02% MeIm solution (3.00 parts by mass, active ingredient 0.0006 parts by mass) were mixed and stirred at 40° C. for 2 hours. The obtained solution was referred to as LRP-SiO2 solution 1.
[0319] Through the above steps, a modified inorganic compound Y in which at least a part of the inorganic compound Y contained in the solution 1 is bonded to at least a part of the NK oligomeric UA-122P is obtained.
[0320] ··Preparation of 1 mass% Fe solution
[0321] 1,1-Bis(diisopropylphosphino)ferrocene (manufactured by Tokyo Chemical Industry Co., Ltd., 1.0 parts by mass) and MEK (methyl ethyl ketone, 99.0 parts by mass) were mixed and stirred thoroughly. The obtained solution was referred to as a 1% by mass Fe solution.
[0322] ··1-Methylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.) (2 parts by mass) and MEK (methyl ethyl ketone, 98 parts by mass) were mixed and stirred thoroughly. The mixture was diluted 10 times twice to obtain a 0.02% by mass MeIm solution.
[0323] Solvent replacement and addition of other ingredients
[0324] MEK (75 parts by mass) was removed from the obtained LRP-SiO2 solution A1 (total parts by mass) using an evaporator (NE-1101, manufactured by Tokyo Rikakii Co., Ltd.).
[0325] Next, the residue was placed in a container, and the residue remaining in the flask was further washed three times with propylene glycol monomethyl ether acetate (PGMEA) and transferred to a container. At this time, a total of 113 parts by mass of PGMEA was used. The solution in the container was fully stirred.
[0326] Addition of other ingredients
[0327] To the solvent-substituted solution, 10% by mass of Ominirad 819 solution (1.90 parts by mass) (manufactured by IGM Resins Co., Ltd.), 10% by mass of Ominirad 127 solution (manufactured by IGM Resins Co., Ltd.) (1.50 parts by mass), 50% by mass of Tinuvin 400 solution (manufactured by BASF) (2.00 parts by mass) and 10% by mass of L7604 solution (1.25 parts by mass) (manufactured by Dow) were further added to prepare Composition 1.
[0328] Compositions other than Composition 1 were prepared by the same procedure as Composition 1 except that the contents of the various components shown in the following table were changed.
[0329] -Formation of resin layer-
[0330] Composition 4 (2.0 mL) was dripped onto one primer layer of the obtained eyeglass lens substrate with a primer layer and spin-coated. During the spin coating, the eyeglass lens substrate with a primer layer coated with Composition 4 was rotated at 500 rpm for 10 seconds, 2000 rpm for 0.5 seconds, and finally 0 rpm for 1 second. Next, the obtained substrate was heated at 100° C. for 20 minutes.
[0331] Furthermore, composition 3 was spin-coated on the coating film of composition 4 in the same procedure as composition 4, and heated at 100° C. for 20 minutes. Composition 2 and composition 1 were spin-coated in the same procedure as above, and a coating film of composition 4, a coating film of composition 3, a coating film of composition 2, and a coating film of composition 1 were formed in that order on one primer layer of the eyeglass lens substrate with a primer layer.
[0332] In addition, for the other primer layer of the obtained eyeglass lens substrate with a primer layer, the same steps as above were followed to form a coating film of Composition 4, a coating film of Composition 3, a coating film of Composition 2, and a coating film of Composition 1 in sequence on the other primer layer.
[0333] Then, a high-pressure mercury lamp (100 mW / cm 2 ) as a light source, each coating film of each composition on both sides of the eyeglass lens substrate was irradiated with ultraviolet light (cumulative light intensity: 0.8 J / cm 2) and then fired at 100°C for 10 minutes to obtain the eyeglass lens of Example 1 having a primer layer, a resin layer 1D, a resin layer 1C, a resin layer 1B and a resin layer 1A in sequence on both sides of the eyeglass lens substrate.
[0334] <Example 2 to Example 4, Comparative Example 1 to Comparative Example 4>
[0335] Examples 2 to 4 and Comparative Examples 1 to 4 were prepared by the same procedure as in Production Method 1, except that the contents of the various components were changed as shown in the following table.
[0336] The numerical values in the table represent parts by mass of various components in each composition.
[0337] TA-100: Silsesquioxane (AC-SQ TA-100, manufactured by Toagosei Co., Ltd.)
[0338] 4130Y: 30 mass % acryl-coated SiO2 nanoparticle dispersion (MEK-AC-4130Y, manufactured by Nissan Chemical Co., Ltd.)
[0339] 122P: Urethane acrylate (compound represented by formula (I), NK oligomer UA-122P, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)
[0340] 232P: Urethane acrylate (compound represented by formula (I), NK oligomer UA-232P, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)
[0341] Omn127: 10 mass % Ominirad127 solution (polymerization initiator V: the molar absorption coefficient was measured by the above method and confirmed to be the predetermined molar absorption coefficient, manufactured by IGM Resin Co., Ltd.)
[0342] Omn819: 10 mass% Ominirad819 (polymerization initiator W: the molar absorption coefficient was measured by the above method and confirmed to be the predetermined molar absorption coefficient, manufactured by IGM Resin Co., Ltd.)
[0343] Tin400: 50 mass% Tinuvin400 (produced by BASF)
[0344] EpiCl: epichlorohydrin (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0345] Fe: 1 mass % Fe solution as above
[0346] AlCl3: 1 mass % AlCl3 solution as above
[0347] ·MeIm: 0.02 mass % MeIm solution as mentioned above
[0348] MEK: Methyl Ethyl Ketone
[0349] ·PGMEA: Propylene glycol monomethyl ether acetate
[0350] · L7604: 10 mass% L7604 solution (manufactured by Dow Chemical)
[0351] [Table 1]
[0352]
[0353] <Evaluation>
[0354] (Adhesion)
[0355] -Adhesion between hard coat layer and primer layer-
[0356] The adhesion between the hard coat layer and the primer layer (Pri.-HC in the following table) was evaluated by a cross-cut tape test according to the following procedure in accordance with JIS-K5600.
[0357] For the spectacle lenses prepared by the preparation method 1, a knife was used to cut slits reaching the spectacle lens substrate at intervals of 1 mm on the convex surface of the spectacle lens to form 100 squares. Next, Scotch tape (manufactured by 3M) was strongly pressed on the hard coating layer with the slits cut, and the Scotch tape was quickly pulled in a 45° direction from the surface with the tape attached with a load of 4 kg to peel it off. Then, the number of squares remaining on the primer layer was counted, and the adhesion between the hard coating layer and the primer layer was evaluated according to the following evaluation criteria.
[0358] A: The number of remaining squares is more than 90.
[0359] B: The number of remaining squares is less than 89
[0360] - Adhesion between hard coat layer and anti-reflection layer -
[0361] The adhesion between the hard coat layer and the antireflection layer (HC-AR in the following table) was evaluated by a cross-cut tape test according to the following procedure in accordance with JIS-K5600.
[0362] On the two surfaces of the hard coating layer of the eyeglass lens produced by production method 1 on the opposite side of the eyeglass lens substrate, a multilayer inorganic antireflection layer (thickness 400nm, composition: SiO2 and ZrO2) is formed by vacuum evaporation (electron beam method) to produce a sample for HC-AR evaluation.
[0363] For the obtained HC-AR evaluation sample, a knife was used to cut out slits reaching the substrate of the eyeglass lens at intervals of 1 mm on the convex surface of the sample to form 100 squares. Next, Scotch tape (manufactured by 3M) was strongly pressed on the anti-reflection layer with the slits cut, and the Scotch tape was quickly stretched from the surface with the tape in a 45° direction with a load of 4 kg to peel it off. Then, the number of squares remaining on the hard coating was counted, and the adhesion of the hard coating to the anti-reflection layer was evaluated according to the same evaluation criteria as the adhesion of the hard coating to the primer layer.
[0364] (crack)
[0365] Three spectacle lenses produced by the production method 1 were produced, and the presence or absence of cracks in the spectacle lenses was visually confirmed. The number of spectacle lenses in which cracks were produced among the three spectacle lenses was evaluated.
[0366] A: The number of cracked eyeglass lenses is 0
[0367] B: The number of cracked eyeglass lenses is 1 to 3
[0368] (Scratch resistance (pencil hardness))
[0369] Using the eyeglass lenses produced by Production Method 1, the pencil hardness of the hard coating layer of each eyeglass lens was measured to evaluate the scratch resistance.
[0370] A pencil was inserted obliquely into the convex surface of the hard coating layer of each of the above-mentioned eyeglass lenses on the side opposite to the primer layer, and the hardness before the scratch was made was taken as the hardness of the hard coating layer. For example, if the hard coating layer was not scratched by a 6H pencil but was scratched by a 7H pencil, the hardness of the hard coating layer was 6H.
[0371] A: Hardness is 7H or above
[0372] B: Hardness below 6H
[0373] (Heat resistance)
[0374] On both surfaces of the hard coating layer on the opposite side of the primer layer of the eyeglass lens produced by production method 1, a multilayer inorganic antireflection layer (thickness 400nm, composition: SiO2 and ZrO2) is further formed by vacuum evaporation (electron beam method) to produce a sample for heat resistance evaluation.
[0375] The obtained sample for heat resistance evaluation is placed in an oven, heated at 60°C for 1 hour, then taken out of the oven and cooled naturally to room temperature. After natural cooling, the obtained sample is visually observed. The heating temperature is raised by 10°C each time, and heated at each heating temperature for 1 hour until the cracks of the heated sample become larger or new cracks are generated compared with the sample before heating (the sample before being placed in the oven). Repeat the above steps. When the cracks of the heated sample become larger or new cracks are generated compared with the sample before heating, the previous heating temperature of the heating temperature is used as the heat resistance temperature and evaluated according to the following evaluation criteria. For example, when the cracks become larger or new cracks are generated after heating at 60°C for 1 hour and at 70°C for 1 hour, the heat resistance temperature is set to 60°C.
[0376] A: Heat resistance temperature is above 90℃
[0377] B: Heat resistant temperature is below 80℃
[0378] In the table, the meanings of each entry are as follows.
[0379] The numerical values in Tables 2 and 3 represent the solid content of each component in each composition.
[0380] The column “mass ratio A (Y / X)” shows the mass ratio A of the content of the inorganic compound Y to the content of the organic compound X.
[0381] The column “Mass ratio B (V / W)” shows the mass ratio B of the content of the polymerization initiator V relative to the content of the polymerization initiator W.
[0382] The column "Thickness (μm)" indicates the thickness of the hard coat layer (total thickness of the resin layers). The thickness is measured by the above method.
[0383] The "balance" in the "Fe" column represents 100 - (the total solid content of various components other than Fe shown in the table).
[0384] The "Configuration" column indicates the arrangement of each resin layer in each hard coating layer. For example, "Primer side 1D → 1C → 1B → 1A" indicates a hard coating layer having resin layer 1D, resin layer 1C, resin layer 1B and resin layer 1A in that order on the primer layer.
[0385] The numerical value in parentheses in "Adhesion" indicates the number of remaining squares / 100 squares.
[0386]
[0387]
[0388] As shown in Table 1, it was confirmed that the spectacle lenses of the present disclosure can obtain the desired effects.
[0389] Explanation of symbols
[0390] 10. Eyeglass lenses
[0391] 12. Eyeglass lens substrate
[0392] 14 Primer layer
[0393] 16 Hard coating
Claims
1. A spectacle lens comprising, in order, a spectacle lens substrate, a primer layer and a hard coating layer, The hard coating layer comprises a plurality of resin layers formed by coating a multilayer composition, The composition comprises an organic compound X selected from the group consisting of polymerizable compounds and polymers thereof, an inorganic compound Y selected from the group consisting of inorganic oxide particles and silsesquioxane, and a polymerization initiator. In the case where the composition includes the polymer, at least a portion of the polymer and at least a portion of the inorganic compound Y may be combined, The spectacle lenses satisfy conditions 1 and 2, Condition 1: The mass ratio A of the content of the inorganic compound Y to the content of the organic compound X in the composition used for forming the plurality of resin layers is different from each other and is 0.7 to 5.3, The mass ratio A of the composition used in forming each of the resin layers constituting the plurality of resin layers gradually increases from the primer layer side toward the side opposite to the primer layer side, Condition 2: The polymerization initiator comprises a polymerization initiator V having a ratio of a molar absorption coefficient at a wavelength of 254 nm to a molar absorption coefficient at a wavelength of 365 nm of 50 or more and a polymerization initiator W having a ratio of the molar absorption coefficient of less than 30, The mass ratio B of the content of the polymerization initiator V to the content of the polymerization initiator W is 0.2 to 0.
8.
2. The eyeglass lens according to claim 1, wherein: The inorganic oxide particles include one or more selected from the group consisting of SiO 2 , Al 2 O 3 , SnO 2 , ZrO 2 , and TiO 2 .
3. The spectacle lens according to claim 1 or 2, wherein: An antireflection layer is also provided on the hard coat layer.
Citation Information
Patent Citations
Eyeglass lens
WO2015163465A1